Building the countryside: a regional perspective on the architecture and settlement of rural Tripolitania from the 1st c. BC to the 7th c. AD - Sheldrick, N (2016)
In this thesis, data collected from both previously published material and new surveys conducted using satellite imagery on the architecture and construction of over 2,400 rural structures in nine different regions of Tripolitania and dating between the 1st c. BC and the 7th c. AD are brought together and analysed on a regional scale. The synthesis and standardisation of these data and the creation of new typologies, applicable to structures in all parts of the region have, for the first time, facilitated meaningful comparisons between buildings and settlements across Tripolitania during the period under the study, in a more systematic fashion and on a wider scale than has previously been possible. This first part of this study contextualises the material with discussions on the historical background of Tripolitania, previous investigations and methodological foundations, the evidence for pre-Roman architectures and settlement, and the chronology of rural settlement during the period under study based on ceramic evidence. This is followed by a discussion of the known military buildings in the region, with particular reference to how these structures related and potentially contributed to the development of civilian settlement and architecture. The second part of this study presents quantitative and qualitative analyses of the physical characteristics of the main group of buildings under investigation: unfortified and fortified farm buildings. Discussions of how different spaces may have been utilised and the spatial relationships between the settlement groups formed by these buildings provide insight into how and why different types of buildings developed in the countryside between the 1st c. BC and the 7th c. AD. These analyses demonstrate that the rural buildings of Tripolitania can be seen as meaningful reflections not only of the wide variety of activities taking place in the buildings themselves, but also of the varying histories and patterns of land-use in different parts of the region and even the status, wealth, and socio-cultural structures of the people who constructed and lived in them.